Design and Simulation of a Fishbone-Shaped Electrostatic Comb Drive Actuator for MEMS Applications - Megat Muhammad Ikhsan Megat Hasnan; Mohd Faizul Mohd Sabri; Suhana Mohd Said; Nik Nazri Nik Ghazali (Science and Technology: Developments and Applications Vol. 1, 2024)
This chapter introduces the design and evaluation of a high force density fishbone-shaped electrostatic comb drive actuator, addressing challenges in conventional microactuator designs for MEMS applications. Electrostatic actuators are widely used due to their ability to produce large displacements at low driving voltages; however, their force density is typically constrained by the large active area required. The proposed fishbone design leverages a branched structure to significantly increase the electrode capacitance without expanding the active area or reducing the electrode gap, thereby enhancing the electrostatic actuation force. A two-dimensional finite element analysis was performed to simulate the actuator’s performance, comparing its drive force and displacement to a conventional straight-sided comb drive actuator under identical conditions. Both designs featured a fixed active area of 800 × 300 µm and a minimum gap of 5 µm. Results revealed that the fishbone actuator achieved a 485% improvement in drive force and significantly enhanced displacement efficiency, owing to its geometry that mitigates lateral instability and maximizes longitudinal actuation force. This study demonstrates the potential of the fishbone-shaped design for compact, high-force MEMS actuators, with promising applications in microgrippers, micropositioning systems, and other precision devices.